Under the never sky - Rossi, Veronica (New York Harper, 2012)
Aria and Perry, two teens from radically different societies--one highly advanced, the other primitive--hate being dependent on one another until they overcome their prejudices and fall in love, knowing they can't stay together--Provided by publisher.
KAL-2977, donated by Ms. Jowana B. Bueser.
Keywords: Prejudices -- Juvenile fiction; Survival -- Juvenile fiction; Friendship in adolescence -- Juvenile fiction